(untitled) (Revista Apotheke, 2026)
This essay presents some notes on the intelligent experience with the Paula Rego Teaching Plan: Giving Fear a Face, offered in the undergraduate course and taught by Professor Jociele Lampert as a partial requirement for Teaching Internship I of the Graduate Program in Visual Arts/Doctorate in the area of concentration Teaching Visual Arts, in the second semester of 2022, based on John Dewey’s book Human Nature and Conduct, which highlights customs and their unfavorable influences on beliefs, emotions, and moral purposes. Specifically, this leads to a separation between habit and thought. In this work, Dewey states that thoughts feed thoughts and not actions in this separative process. Consequently, current methods in education multiply an imitative democracy of opportunities by not creating conditions for functional thinking. And art, in this sense, becomes poorer by depreciating the moral value of the arts. However, by providing instruction in the deliberative art of energies, with a harmonization of constructive forms, the investigative path in the teaching of painting makes use of a moral sense in the perspective of enabling practical skills to lead to the exercise of thought in an intelligent experience.